1987
DOI: 10.1007/bf01907221
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and regional vascular effects of atrial natriuretic peptide in a rat model of chronic heart failure

Abstract: To characterize the systemic and regional vascular effects of atrial natriuretic peptide (ANP) in chronic heart failure, central hemodynamics, regional blood flow and plasma ANP levels were determined in a rat model of myocardial infarction and failure and in sham-operated animals. Measurements were made in the conscious state before and after intravenous rANP [99-126] (8 micrograms bolus followed by continuous infusion of 1.0 microgram/kg/min). With this protocol, ANP significantly decreased cardiac output, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Hirooka et al 23 examined the question of whether there is a difference in the direct forearm vasodilatator effect of intra‐arterial ANP infusion in patients with heart failure and normal subjects and demonstrated a marked attenuation of this effect in patients with heart failure compared with normal subjects. These results are consistent with the results of a preliminary report on a study of patients and animals with heart failure that suggest that vascular responses to ANP are blunted in heart failure 24,25 . However, the mechanism of this attenuation of the ANP‐induced vasodilatator effect in heart failure is unknown.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Hirooka et al 23 examined the question of whether there is a difference in the direct forearm vasodilatator effect of intra‐arterial ANP infusion in patients with heart failure and normal subjects and demonstrated a marked attenuation of this effect in patients with heart failure compared with normal subjects. These results are consistent with the results of a preliminary report on a study of patients and animals with heart failure that suggest that vascular responses to ANP are blunted in heart failure 24,25 . However, the mechanism of this attenuation of the ANP‐induced vasodilatator effect in heart failure is unknown.…”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with the results of a preliminary report on a study of patients and animals with heart failure that suggest that vascular responses to ANP are blunted in heart failure. 24,25 However, the mechanism of this attenuation of the ANP-induced vasodilatator effect in heart failure is unknown. The present study suggests one possibility, namely that the attenuated vasodilatator effect of ANP in patients with heart failure may be attributable to impaired endothelial function found in heart failure, because previous investigators have shown that agonist-induced NO-mediated vasodilatation in response to muscarinic stimulation is impaired in the peripheral circulation of patients with heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, natriuretic peptide signaling gains greater prominence in heart failure as plasma natriuretic peptide concentrations become markedly elevated (Burnett, Jr. et al, 1986; Sugawara et al, 1988; Tikkanen et al, 1985). Vasodilatory and diuretic responses to ANP are blunted in heart failure animal models (Drexler et al, 1987; Riegger et al, 1988) and in heart failure patients (Cody et al, 1986; Hirooka et al, 1990; Tsutamoto et al, 1993). The blunted response has been attributed by some to a reduction in NPR-A expression, as seen in the pulmonary vasculature of heart failure patients (Tsutamoto et al, 1992) and in the systemic vasculature of rats models of high-output heart failure (Garcia et al, 1992).…”
Section: Pathophysiological Role Of Cgmp Signaling In Cardiovasculamentioning
confidence: 99%
“…1994a). As a result of increased sympathetic outflow, systemic vacular resistance is increased (Drexler et al . 1987) and may contribute to the high mortality in this heart failure rat model (Pfeffer et al .…”
mentioning
confidence: 99%